Concentrations of mercury and other trace elements in porbeagle shark Lamna nasus. Issue 1 (15th November 2016) - Nicolaus, E.E. Manuel; Bendall, Victoria A.; Bolam, Thi P.C.; Maes, Thomas; Ellis, Jim R.
Abstract: Concentrations of 11 trace elements in three tissues of porbeagle shark Lamna nasus (n = 33) were determined. The maximum observed concentrations of Cd and Pb in muscle were 0.04 and 0.01 mg kg − 1, respectively, and all muscle samples were below European seafood limits for these metals. Hg concentrations in either the red or white muscle that exceeded European regulations for seafood were observed in one-third of specimens. Hg concentration, however, increased with length, and all fish > 195 cm had concentrations > 1.0 mg kg − 1, with a maximum observed value of 2.0 mg kg − 1 . Concentrations of Fe and Cu were, on average, 9.7 and 10 times higher in red muscle than in nearby white muscle, respectively. Mn, Zn, As and Se were also found in significantly higher concentrations in red muscle than in white muscle. Highlights: Analysed 11 trace elements in three tissues of porbeagle shark Lamna nasus Maximum concentrations of Cd and Pb in muscle were 0.04 and 0.01 mg kg − 1 . Hg concentrations increased with length All porbeagle > 195 cm had concentrations > 1.0 mg kg − 1 .